An animal model for the study of Chamomilla in stress and depression: pilot study - Gordinho Pinto, Sandra Augusta; Bohland, Elisabeth; de Paula Coelho, Cideli; Furquim de Azevedo Morgulis, Maria Sílvia; Bonamin, Leoni Villano (Homeopathy, 2008)
The behavioral and hematological effects of treatment with Chamomilla 6cH in mice subjected to experimental stress are described. Swiss mice were randomly divided into pairs, one animal was inoculated with Ehrlich's tumor, the other was treated daily with Chamomilla 6cH or control or received no treatment. After 7 days, the animals were observed in an open-field arena and blood samples taken. Mice who cohabitated with a sick cage-mate showed a decrease in their general activity, but those treated with Chamomilla 6cH were less severely affected (p = 0.0426). No hematological changes were observed.In a second experiment, the forced swimming test was applied to mice pre-treated with Chamomilla 6cH, controls were: water, 10% ethanol or amitriptyline. Only the amitriptyline and ethanol treated groups showed significant excitatory behavior (p = 0.0020), Chamomilla 6cH treated animals' scores intermediate between water control and ethanol or amitriptyline. A decrease in the leukocyte count was observed in the amitriptyline and Chamomilla 6cH treated groups (p = 0.039). These data suggest that treatment with Chamomilla 6cH is related to the recovery of basal behavioral conditions in mice subjected to stressful conditions.
Keywords: Chamomilla; homeopathy; behavior; neuro-immune-modulation